2017
DOI: 10.1002/aur.1852
|View full text |Cite
|
Sign up to set email alerts
|

Altered attentional processing in male and female rats in a prenatal valproic acid exposure model of autism spectrum disorder

Abstract: We studied rats prenatally exposed to valproic acid (VPA), an established rodent model of autism. Both male and female VPA rats had a range of attentional impairments with sex-specific characteristics. Importantly, with fixed rules, graded difficulty levels, and more time, VPA rats could be successfully trained on the attentional task. Our work validates the use of the VPA model in the quest for evaluating suitable therapeutic targets for improving attentional performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 89 publications
0
19
1
1
Order By: Relevance
“…Similarly, in another study, males made more premature responses (impulsive action) when the ITI was long [33]. Additionally, male rats were found to be more impacted by a variable ITI, leading to more impulsive errors in 5CSRTT, while female performance remained robust, even in the face of increasing task difficulty [38]. However, another study using a two-choice task found that with increasing difficulty (long ITI), in adolescence, males were more impulsive than females, while as adults, females made more premature responses as compared to males [37].…”
Section: Sex Differences In Animals In Attention and Impulsive Actionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, in another study, males made more premature responses (impulsive action) when the ITI was long [33]. Additionally, male rats were found to be more impacted by a variable ITI, leading to more impulsive errors in 5CSRTT, while female performance remained robust, even in the face of increasing task difficulty [38]. However, another study using a two-choice task found that with increasing difficulty (long ITI), in adolescence, males were more impulsive than females, while as adults, females made more premature responses as compared to males [37].…”
Section: Sex Differences In Animals In Attention and Impulsive Actionmentioning
confidence: 73%
“…An investigation into prenatal drug use found that methamphetamine or methylphenidate given to dams during pregnancy affected the offspring, with both drugs increasing impulsive action in the offspring, with only very subtle sex differences observed [110]. Similarly, in an animal model used to examine autismrelated endophenotypes, valproic acid administration to pregnant dams increased inattention, with no effect on impulsivity, in both male and female offspring, with very minor task-dependent sex differences noted [38].…”
Section: Programmingmentioning
confidence: 99%
“…Following prenatal valproic acid (VPA) treatment, an animal model of autism, male mice show impairments in social behavior in adulthood, while female mice do not (Kim et al, 2013 ). The prenatal VPA model also leads to male-specific deficits in sensorimotor gating, another phenotype of ASD (Anshu et al, 2017 ). Similar male-specific effects are seen in the telomerase reverse transcriptase overexpressing mice (TERT-tg).…”
Section: Sex Differences In Glutamate Systems In Diseasementioning
confidence: 99%
“…On the other hand, increased repetitive/stereotyped behaviors was observed in both male and female VPA-exposed rats [ 35 ]. In the visuospatial attention and sensorimotor gating behaviors, both male and female VPA rats showed similar levels of abnormalities with minor differences in specific parameters [ 36 ]. Mice exposed to VPA also exhibited a male-prevalent social deficit, manifested by reduced sniffing of a stranger mouse in the three-chamber assay, although both sexes have similar abnormalities in the open field and elevated plus maze tasks [ 37 ].…”
Section: Sex Differences In Environmental Models Of Autismmentioning
confidence: 99%